HUBUNGAN ANTARA TINGKAT PENGETAHUAN PERAWAT DENGAN PERILAKU PENCEGAHAN PENULARAN DARI KLIEN HIV/AIDS DI RUANG MELATI 1 RSUD DR MOEWARDI SURAKARTA - Fina Mahardini; Arina Maliya (Universitas Muhammadiyah Surakarta, 2009)
The intensive interaction between HIV/AIDS clients and nurses makes nurses face the opportunity of infection from clients. Implementing the prevention behavior can be a way to prevent this spreading. Nurses’ behavior and action can be affected by some factors, for example is knowledge.This research’s objective is to analyze the correlation between nurses’ knowledge and transmission preventing-behavior from HIV/AIDS clients in Melati 1 Ward of Dr. Moewardi Province General Hospital of Surakarta. Method used in this research is correlation with cross-sectional approach. Respondents in this research number in 23 people chosen by means of population study method. Data were collected by means of questionaire and checklist. Data analysis used in this research is Spearman’s Rank Correlation Test using the version 11.0 of SPSS. Based upon the result of this research, the conclusions are: (1) Most of respondents are in the category of good knowledge level (86,98%). (2) Most of respondents are in the category of good transmission preventing-behavior (69,6%). (3) There is a significant correlation between knowledge and transmission preventing-behavior from HIV/AIDS clients in Melati 1 Ward of Dr. Moewardi Province General Hospital of Surakarta, proved by probability value from spearman’s rank correlation test 0,003, lower than probability value (0,05)